Hubungan Perkembangan Sosial Dengan Kesehatan Mental Pada Anak Usia Sekolah - Agus Hidayat; Luthfiah Chusnul Khotimah; Nurul Istiqomah; Anik Enikmawati; Muhammad Anis Sumaji (Journal Pharma Saintika, 2021)
Background: School age children are children aged 7-12 years.There are several factors that affect children's mental health, including external and physical factors internally.Destination: Knowing the relationship between social development and mental health in school-age children.Methodology: This study used a cross sectional study of 65 respondents. The sampling technique was probability sampling. This research instrument used a questionnaire, the analysis used was the chie-square test. Results: The results showed that there was a relationship between social development and mental health in school-age children (p value 0.001 < 0.005). Conclusion: Total Research respondents were 65 students of SDN Karangwuni with the age of 7-8 years as many as 21 people (32.3%), age 9-10 years as many as 24 people (37.0%), age 11-12 years as many as 20 people (30.7% )2. social development with sufficient category as many as 37 respondents (56.9%) and good category as many as 28 respondents (43.1%)3. For mental health, it shows that mental health in the normal category is 42 respondents (64,5 %) and the abnormal category is 23 respondents (35.4%). There is a relationship between social development and mental health in school-age children using the Chi-square test and it is found that the p-value is 0.01.